A new protocol for evaluating the efficacy of some dispensing systems of a packaging in the microbial protection of water‐based preservative‐free cosmetic products. (2nd June 2015) - Devlieghere, F.; De Loy‐Hendrickx, A.; Rademaker, M.; Pipelers, P.; Crozier, A.; De Baets, B.; Joly, L.; Keromen, S.
Synopsis: Objective: A new protocol is described for assessing the efficacy of the dispenser of some packaging systems (PSs) of preservative‐free cosmetic products in protecting both their contained formula and their delivered doses. Methods: Practically, aiming at mimicking contacts with a non‐sterile skin or fingers, the dispensing system is put into contact with a pre‐contaminated fabric by a standardized colonization of P. aeruginosa . Results: When applied to three different types of packaging, results show clear differences in both criteria between these conditioning articles, that is variable efficacies in protecting the contained product and the delivered doses, knowing that the first aspect is of paramount importance. Conclusion: The proposed protocol is proved being able to discriminate between different PSs and provides information on strong and weak features of certain types dispensing technologies prone to efficiently decrease either the dose contamination or to prevent contamination in reaching the contained product. Therefore, the proposed protocol can contribute to an objective selection of a PS for protecting a cosmetic care product with a low content of preservative or preservative free.